Entre nativos e exóticos: a mestiçagem na construção de uma nova identidade na caprinovinocultura dos sertões - Junior, Oswaldo Gonçalves (2015)
In the Northeastern Semiarid of Brazil, dynamic among creators of goats and sheep native and exotic bring a range of meanings. In addition to actual trade disputes, conflicts are waged in the realm of ideas, revealing different values and interests around the racial origin of these animals. Between these two segments lies most of the small farmers and the traditional Semiarid sheep and goat raising, based on the use of animals breed, arising from the dynamics of spontaneous crossings, own extensive creations characterized by reduced control over the herds, state which shows a marked contrast to the first two segments. Given that their influence on a traditional creations can result in improved production of small farmers, linked to different social sector research and extension have turned their efforts to construct possible arrangements that are satisfactory to the reversal of historical problems of the region, especially the use of animal miscegenation as a strategy for change. It focuses on the work of these actors, the forms of interaction between them, fulfill the role that ideas, values and attitudes in the face of the possibilities for sheep and goat raising that region.